A lexical-semantic perspective of the cholo in Lima, hora cero and Kikuyo by Enrique Congrains - Paz Campuzano, Oscar (2022)
The article studies the cholo in Lima, hora cero (1954) and Kikuyo (1955), the first books of short stories by Peruvian writer Enrique Congrains Martin. Based on the textual references identified in both publications, the article analyzes the lexical-semantic proposal of the term cholo in the context of 20th century Peru, according to Congrains, an urban storyteller of the "Generation of the 50's". The linguistic analysis concludes that Congrains' narrative presents a lexical-semantic variety of the term cholo by recognizing an ethnic-racial meaning and another in the socio-cultural order. In addition, it is observed that cholo is a notion used to generalize the popular sectors and to express a sense of community, whose members do not repel each other racially or socially.